Navigating cholestasis: identifying inborn errors of bile acid metabolism for precision diagnosis - Nittono, Hiroshi; Suzuki, Mitsuyoshi; Suzuki, Hiromi; Sugimoto, Satoru; Mori, Jun; Sakamoto, Rieko; Takaki, Yugo; Hayashi, Hisamitsu; Takei, Hajime; Kimura, Akihiko (Frontiers in Pediatrics, 2024)
Inborn errors of bile acid metabolism (IEBAM) cause cholestasis during the neonatal period, and 8 types of IEBAM have been reported to date. IEBAM accounts for approximately 2% of cases of cholestasis of unknown cause. As only 10 patients have been identified in Japan, IEBAM presents diagnostic challenges due to the similarity of clinical symptoms with biliary atresia, thus necessitating precise differentiation to avoid unnecessary invasive procedures. Laboratory tests in IEBAM are characterized by normal γ-glutamyltransferase (GGT) and serum total bile acid (STBA) levels despite the presence of cholestasis; therefore, measuring STBA and GGT is essential to distinguishing biliary atresia from IEBAM. With suspected IEBAM, liquid chromatography-mass spectrometry (LC/MS) analysis of urinary bile acids is needed to optimize diagnostic and therapeutic efficacy and avoid open cholangiography and initiate treatment for primary bile acids such as cholic acid or chenodeoxycholic acid. This prospective report aims to increase awareness of IEBAM by highlighting the characteristics of general blood test and bile acid profiles from LC/MS analyses of blood, urine, and stool samples.